Releasing international prisoners - Mulgrew, Roisin (Wolf Legal Publishers, 2014)
This book chapter analyses the rules and procedures that govern the release of international prisoners (persons convicted for the commission of international crimes by international criminal courts) at the International Criminal Court (ICC) and the Mechanism for the International Criminal Tribunals (MICT). It begins by setting out the legal framework governing release decisions at the MICT and ICC and proceeds with discussions of key elements of this framework, namely, eligibility for release, the procedure used to make release decisions and the criteria that judges have to consider in reaching their decision. It also analyses the subtle yet strong potential influence that states can have on the exercise of judicial discretion in the international criminal justice system.